Pengaruh Brand Awareness, Brand Association, Perceived Quality Terhadap Brand Loyalty Pada Produk OPPO Smartphone Di Jaya Ponsel Payakumbuh - Muhammad Faisal; Febsri Susanti (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This research was conducted to determine the effect of brand awareness, brand association, perceived quality on brand loyalty on OPPO Smartphone products in Jaya Ponsel Payakumbuh. This research method uses quantitative methods. The technique used in collecting data in this research is a questionnaire by distributing questionnaires to 96 respondents using OPPO in Jaya Ponsel Payakumbuh, and the data from the respondents' answers will be processed using SPSS. The results of this study indicate that brand awareness has a positive effect on brand loyalty, brand association has a positive effect on brand loyalty, and perceived quality has a positive effect on brand loyalty.